O ciszy i milczeniu w piosenkach rockowych - Barnaś, Paulina (Dydaktyka Polonistyczna, 2017)
The article in its introductory part outlines the history of rock music in Poland and presents the tools to be used in the analysis of the lyrics of rock songs, which the author carries out in the main body of the paper. Selected rock songs of Polish music groups from the 1960s to the 1980s are analysed with reference to the motif of silence present in them and to its functionality in connection with the musical arrangements.